Natural quinones and their analogues: synthesis, intracellular redox cycling and identification of indoleamine-2,3-dioxygenase (IDO) as a potential target for anticancer activity - Blunt, Christopher; Torcuk, Canan; Liu, Yang; Lewis, William; Siegel, David; Ross, David; Moody, Christopher J. (Wiley-VCH Verlag, 2015)
Natural quinones, often linked with cellular oxidation processes, also exhibit pronounced biological activity. In particular, the structurally unique isothiazolo-naphthoquinone, aulosirazole, isolated from blue-green alga, possesses selective antitumor cytotoxicity, although its mechanism of action is unknown. The first synthesis of aulosirazole is now described, using a route centered upon a late stage regioselective Diels-Alder reaction. The structurally related natural product pronqodine A, an inhibitor of prostaglandin release, and analogues thereof, were also prepared for comparison. Biological evaluation of the compounds identified one potential target as the immunoregulatory enzyme indoleamine-2,3-dioxygenase (IDO). The isothiazolo-quinones are also efficient substrates for the human quinone reductase NQO1, and undergo intracellular NQO1-dependent redox cycling resulting in the generation of reactive oxygen species, and at lower doses have the potential to alter the ratio of intracellular oxidized to reduced pyridine nucleotides.